Diverse Exotic Orders and Fermiology in Fe-Based Superconductors: A Unified Mechanism for B1g/B2g Nematicity in FeSe/(Cs,Rb)Fe2As2 and Smectic Order in BaFe2As2 - Onari, Seiichiro; Kontani, Hiroshi (Frontiers in Physics, 2022)
A rich variety of nematic/smectic orders in Fe-based superconductors is an important unsolved problem in strongly correlated electron systems. A unified understanding of these orders has been investigated for the last decade. In this article, we explain the $B_{1g}$ symmetry nematic transition in FeSe$_{1-x}$Te$_x$, the $B_{2g}$ symmetry nematicity in AFe$_2$As$_2$ (A=Cs, Rb), and the smectic state in BaFe$_2$As$_2$ based on the same framework. We investigate the quantum interference mechanism between spin fluctuations by developing the density wave equation. The observed rich variety of nematic/smectic orders is naturally understood in this mechanism. The nematic/smectic orders depend on the characteristic shape and topology of the Fermi surface (FS) of each compound. (i) In FeSe$_{1-x}$Te$_x$ $(n_d=6.0)$, each FS is very small and the $d_{xy}$-orbital hole pocket is below the Fermi level. In this case, the small spin fluctuations on three $d_{xz}$, $d_{yz}$, and $d_{xy}$ orbitals cooperatively lead to the $B_{1g}$ nematic $(\q=\bm{0})$ order without magnetization. The experimental Lifshitz transition below the nematic transition temperature $(T_S)$ is naturally reproduced. (ii) In BaFe$_2$As$_2$ $(n_d=6.0)$, the $d_{xy}$-orbital hole pocket emerges around M point, and each FS is relatively large. The strong spin fluctuations due to the $d_{xy}$-orbital nesting give rise to the $B_{1g}$ nematic $(\q=\bm{0})$ order and the smectic $[\q=(0,\pi)]$ order, and the latter transition temperature ($T^*\sim 170$K) exceeds the former one ($T_S\sim140$K). (iii) In heavily hole-doped AFe$_2$As$_2$ $(n_d=5.5)$, the large $d_{xy}$-orbital hole pocket and the four tiny Dirac pockets appear due to the hole-doping. The $B_{2g}$ nematic bond order emerges on the $d_{xy}$-orbital hole pocket due to the same interference mechanism. The present paramagnon interference mechanism provides a unified explanation of why the variety of nematic/smectic orders in Fe-based superconductors is so rich, based on the well-established fermiology of Fe-based superconductors.